Can we rely on public data as a source of information for cancer registry in developing countries? - Shahryar SEMNANI,; Mohammad Javad KABIR,; Sima BESHARAT,; Nafiseh ABDOLAHI,; Ahmad DANESH,; Danyal ROSHANDEL, (Turkish Journal of Gastroenterology, 2019)
-